E-Prescription Implementation: An Analytical Study On The Transformation Of Medical Records From Physical To Electronic - Widyantoro, Rolly Catur; Oktamianti, Puput (Jurnal EduHealth, 2024)
In this study, we explore the success of implementing an e-prescription system in the case of electronic medical records, and the factors that influence it. The introduction explains the importance of e-prescribing in increasing the efficiency and accuracy of the treatment process in health facilities. The method used involved observations of 40 journals covering various approaches, from qualitative to quantitative, with a focus on system design, management support, staff training, technology infrastructure, user participation, system development models, evaluation and maintenance, and user perceptions. This research uses a descriptive analytical approach by collecting data from various literature sources and previous research related to the implementation of e-prescriptions. Data were analyzed to identify challenges, benefits and development strategies in the use of e-prescriptions in the context of transforming medical records from physical to electronic. The research results show that the application of e-prescriptions has the potential to improve operational efficiency, patient safety and service quality. However, there are still obstacles related to user readiness, evaluation effectiveness, and e-prescription system development that need to be overcome. The discussion highlights the need to increase user readiness, evaluate the effectiveness of using e-prescriptions, as well as system development strategies that are appropriate to technological developments and user needs. Collaboration between stakeholders is also considered important in achieving successful e-prescription implementation. Taking these findings into account, coordinated and sustainable efforts are needed to increase the use of e-prescriptions in the context of transforming medical records into electronic form. By overcoming existing challenges and implementing appropriate strategies, it is hoped that the implementation of e-prescribing can make a significant contribution in improving the quality of health services and patient safety.